Business Ethics And Values : Individual, Corporate and International Perspectives - FISHER, Colin (Prentice-Hall, 2006)
A comprehensive look at the fascinating and complex subject of ethics in business that is both theoretically rich and engaging.Fisher and Lovell focus on developing ethical awareness and give as much importance to individual conscience at work as they do to socially responsible behaviour at the corporate level and within the global business world. Business Ethics and Values is suitable for any Business related Ethics, Sustainability or Corporate Social Responsibility course at an upper level undergraduate or Masters level.